SAS survival guide the ultimate guide to surviving anywhere - Wiseman, John (Collins gem, 2020)
The ultimate guide to survival, this edition now includes the most essential urban survival tips for today, supplementing the fully updated original, bestselling handbook. The original and best survival guide for any situation in every climate is back. Now with added techniques for handling Urban dangers, the SAS Survival Handbook is the complete companion for adventurers everywhere. From making camp and finding food in the wild to security and self-defence in the streets, be prepared in any city, land or sea.